2015
DOI: 10.1007/s12010-015-1689-9
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Antioxidant Peptides Derived from Marine Resources: The Sources, Characteristic, Purification, and Evaluation Methods

Abstract: Marine organisms are rich sources of structurally diverse bioactive nitrogenous components. In recent years, numerous bioactive peptides have been identified in a range of marine protein resources, such as antioxidant peptides. Many studies have approved that marine antioxidant peptides have a positive effect on human health and the food industry. Antioxidant activity of peptides can be attributed to free radicals scavenging, inhibition of lipid peroxidation, and metal ion chelating. Moreover, it has also been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 68 publications
(70 reference statements)
1
62
0
3
Order By: Relevance
“…For example, Dávalos et al (2004) have reported that Cys residues have antioxidative activity, as a Cys -SH group in a peptide acts as an effective hydrogen donor to free radicals (Wu et al 2015). In addition, Pro and Gly residues are commonly found in antioxidative peptides from various sources (López-Barrios et al 2014;Wu et al 2015). Furthermore, a high correlation commonly occurs between reducing power and antioxidative activity in some antioxidative peptides (Zhang et al 2009).…”
Section: Characterization Of the Antioxidative Peptidementioning
confidence: 99%
See 2 more Smart Citations
“…For example, Dávalos et al (2004) have reported that Cys residues have antioxidative activity, as a Cys -SH group in a peptide acts as an effective hydrogen donor to free radicals (Wu et al 2015). In addition, Pro and Gly residues are commonly found in antioxidative peptides from various sources (López-Barrios et al 2014;Wu et al 2015). Furthermore, a high correlation commonly occurs between reducing power and antioxidative activity in some antioxidative peptides (Zhang et al 2009).…”
Section: Characterization Of the Antioxidative Peptidementioning
confidence: 99%
“…2b), which are usually related to antioxidative activity (Wu et al 2015). In addition to antioxidative activity, other bioactivities, such as inhibitory activities toward angiotensin I-converting enzyme and dipeptidyl peptidase-IV, have been demonstrated in feather hydrolysate (Fontoura et al 2014).…”
Section: Characterization Of the Antioxidative Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…In reviews on marine bioactive peptides, enzymatic hydrolysates and antioxidant peptides of fish and their processing by-products often overshadowed those of edible marine invertebrates [18,29,46,47]. In this review, we focus on antioxidant peptides purified and identified from enzymatic hydrolysates of edible marine invertebrates, including those prepared by using in vitro gastrointestinal digestion.…”
Section: Introductionmentioning
confidence: 99%
“…Показано, что пептиды, полученные из гидроли-затов белков морских организмов, например мидий, морского угря, микроводорослей, морских ежей, выступают в качестве потенциальных антиоксидан-тов [30,40,72,74,76]. Антиоксидантная активность биологически активных пептидов связана с нали-чием в их составе гидрофобных аминокислот, не-которых ароматических аминокислот и гистидина.…”
Section: фармакологические эффекты пептидов из морских организмовunclassified